Prevalence of sleep disorders among shift and day workers in industrial workers of North Guwahati, Assam - Krishnatreya, Mousumi; Borah, Rinku (International Journal Of Community Medicine And Public Health, 2022)
Background: General sleep disorder and comorbid sleep disorder are highly prevalent in industrialized societies of India because of the work hours that displaces the sleep timing. There is rapid rise of Industries in the North Eastern region of the country, but research have been conducted on a sparse proportion of the population in this area. Aim of the study is to compare the prevalence of sleep disorder in shift worker and day worker based on international classification of sleep disorders (ICSD) criteria in a sample drawn from the working population of industries in North Guwahati, Assam. Methods: Data was collected by administering a set of well validated questionnaire on a sample of 161 shift workers and 161 permanent day workers from 16 industries, from July to December 2021. Additional data concerning demographic profile were also analysed. Results: Among the shift workers and day workers prevalence of general sleep disturbance was 34% and 19% respectively. Prevalence of insomnia, restless leg syndrome was found to be higher among the shift workers compared to day workers. Conclusions: Shift workers experienced more difficulties with the variability of their sleep times. It was associated with a higher prevalence of ICSD-defined symptoms of sleep disorders like insomnia, obstructive sleep apnea and restless leg syndrome. Thus, the study may play a role in occupational health intervention aimed at reducing sleep problems and improving the resilience of shift worker especially in the areas of new industrial development.